ANEMIA KEKURANGAN (DEFISIENSI) ZAT BESI BAYI - Aida Amelda; Hanifah Maani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Anemia usually happened in childhood. Babies 6–12 years old as are those group that are sensitive to iron deficiency anemia (IDA)Hemoglobin is a mean corpuscular volume (MCV), red-cell distribution width (RDW) examination with blood film evaluation that canbe used to screen IDA, especially in high risk babies. This study was carried out by the cross sectional method in healthy babies 6-12years old in Padang city, on November 2006 until January 2007. They were examined in the Clinical Pathology Laboratory of Dr. MDjamil hospital Padang. The samples consisted of 2 ml venous blood EDTA and laboratory examinations. The results were Hb, MCV,and RDW with ABX micros 60. Also blood film evaluation if Hb were 11g/dL. The means of Hb, MCV and RDW were 11.1 ± 1.07 g/dL,71.7 ± 4.70 fl and 14. 2 ± 1.37%. In 62 (45.9%) babies were anemic as a result of IDA examination and the rest of 33 babies (532%) the blood film were normocytic normochromic 49% and normocytic hypochromic (+), mild anisocytosis 51%. In Padang city theIDA examination in 6-12 years old babies were high frequencies in grade I and II by blood film method